2013
DOI: 10.1186/1749-8104-8-7
|View full text |Cite
|
Sign up to set email alerts
|

AKT activation by N-cadherin regulates beta-catenin signaling and neuronal differentiation during cortical development

Abstract: BackgroundDuring cerebral cortical development, neural precursor-precursor interactions in the ventricular zone neurogenic niche coordinate signaling pathways that regulate proliferation and differentiation. Previous studies with shRNA knockdown approaches indicated that N-cadherin adhesion between cortical precursors regulates β-catenin signaling, but the underlying mechanisms remained poorly understood.ResultsHere, with conditional knockout approaches, we find further supporting evidence that N-cadherin main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 55 publications
4
83
0
Order By: Relevance
“…The PDK1-Akt pathway contributes to the regulation of proliferation, survival, differentiation of, and metabolism in various cell types (22,25,36), but its role in neuronal migration has been unclear. We demonstrated a role for the PDK1-Akt pathway in neocortical neurons through the specific manipulation of postmitotic cells with the use of Nex Cre/+ mice or a Neurod1 promoterdependent Cre expression plasmid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PDK1-Akt pathway contributes to the regulation of proliferation, survival, differentiation of, and metabolism in various cell types (22,25,36), but its role in neuronal migration has been unclear. We demonstrated a role for the PDK1-Akt pathway in neocortical neurons through the specific manipulation of postmitotic cells with the use of Nex Cre/+ mice or a Neurod1 promoterdependent Cre expression plasmid.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the extracellular matrix component laminin γ1 and its integrin receptor might function upstream of the PDK1-Akt pathway during neuronal migration (46). Furthermore, given that N-cadherin mediates neuron-glial cell adhesion and regulates Akt activation (36,47), Akt might be activated at sites of such adhesion in an N-cadherindependent manner. Although previous work suggested that Akt might function downstream of Reelin during cortical development (38), PDK1 ablation resulted in a layering defect distinct from that of reeler mutants, suggesting that Akt is not a central effector of Reelin signaling, at least during radial neuronal migration.…”
Section: Gsk3βmentioning
confidence: 99%
“…37,40,41 Furthermore, loss of function of N-cadherin by the conditional knockout (KO) and short hairpin RNA (shRNA) in the cerebral cortex, causes premature differentiation of NPCs. 84, 93 These results demonstrate that N-cadherin plays a critical role in the self-supportive niche to keep the identity of NPCs.…”
Section: Contribution Of N-cadherin To Niche Formationmentioning
confidence: 80%
“…Therefore, we evaluated the effect of MK2206 on the phosphorylation status of Akt and several of its downstream targets, including AMP-activated protein kinase (AMPK), ␤-catenin, CREB-1, endothelial nitric oxide synthase (eNOS), extracellular signal-regulated kinase (ERK), focal adhesion kinase (FAK), glycogen synthase kinase 3 (GSK3), HSP27, P70S6, PRAS40, TOR, and WNK1 (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) in NCI-H1666 cells infected with A/Helsinki/P14/2009 for 0.5 h in the presence of absence of MK2206 and using mock-infected cells as controls. Phospho-proteome profiling revealed that MK2206 treatment did not affect the phosphorylation status of Akt but lowered the phosphorylation levels of its targets, PRAS40 and WNK1 ( Fig.…”
Section: Agentmentioning
confidence: 99%